MINAT WISATAWAN DOMESTIK UNTUK BERKUNJUNG KE PANTAI PASIR PADI PANGKALPINANG - Martina Martina; Juhari Juhari (LPPM STIE PERTIBA Pangkalpinang, 2021)
This study aims to determine the effect of location, promotion, and brand image on the decision to visit. The population in this study are visitors to Pasir Padi Beach, this study uses quantitative research, the data collection method that will be used in this study is by using a questionnaire that is filled out directly by respondents who visit the Pasir Padi Beach tourist attraction in Pangkalpinang. The testing technique in this study uses multiple linear regression analysis to find out that the variables of location, promotion, and brand image have a positive and significant effect on purchasing decisions. The results of the F test show that the independent variables jointly have a positive effect on the dependent variable being accepted. The coefficient of determination (R Square) shows that location, promotion, and brand image can influence the decision of domestic tourists to visit by 51.6%, while the remaining 48.4% is explained by other variables outside the research model.